A gênese documental de professoras em um trabalho colaborativo remoto para o ensino de juros compostos com o uso do GeoGebra - Almeida, Chrystian Bastos de (2022)
This thesis has the general objective to characterize the Documentary Genesis of two High School Mathematics teachers in a remote collaborative work for the teaching of Compound Interest articulated with the GeoGebra software. As a theoretical reference for the development of the research, the Documental Approach of the Didactic was adopted, which has as reference the documental work developed by the teacher when planning his class, and this documentation is the basis of the pedagogical practices implemented by the teacher and his professional improvement. This approach involves the process called Documentary Genesis, in which resources, associated with usage schemes, are transformed into documents. Thus, we analyzed the instrumentation/instrumentalization dialectic, “mother”/“son” resource and productive activity/constructive activity of the teachers' documentary genesis. Complementary theoretical contributions such as the Theory of Conceptual Fields, the Theory of Instrumental Orchestration and the concept of Self-Efficacy were used to deepen the analyses. For the development of the study, of a qualitative nature, we adopted as a methodological reference the reflective investigation, in a remote collaborative context of teachers. In the reflective investigation methodology, there is a dynamic commitment of the teacher, which favors a reflective attitude, as he is led to detail his own activity, sharing with others. The concept of documentary trajectory was also considered, seeking to understand the evolution of documentary work over time. In this research, we focused on the analysis of the documentary work of two teachers who integrated several resources for the teaching of Compound Interest, including the GeoGebra mathematical software. The results show that the teachers showed improvement of knowledge related to the teaching of Compound Interest, from the interaction developed in the collaborative work. Progress was made in the teachers' documental work, highlighting the metamorphosis of their resource system, the enrichment of their individual schemes, as well as the impact on their degree of self-efficacy for teaching Compound Interest